DECISION MAKING PATTERN AND CONTRIBUTION OF FAMILY LABOR IN PALM OIL FARMING: CASE STUDY DISTRICT OF PONDOK KELAPA BENGKULU TENGAH REGENCY - Wulandari Wulandari; Ketut Sukiyono; Sriyoto Sriyoto (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2020)
This study is aimed at investigating the household decision pattern in oil palm farming activities, analysing the household member labor and wage labor contribution to labor need. This study uses descriptive analysis methods an interview 90 palam oil households randomly selected. Decision-making patterns apply Sajogyo’s households decision-making pattern. This research was conducted in the District of Pondok Kelapa on March 25 - April 25 2019. The study found that decision-making in the households related to oil palm farming is dominated by the husband, as well as the implementation of farming activities. The research also concludes that husband contributes more than his wife in fullfiling labor needs. The contribution of wage labor results in dominating men wage labor. However, household labor has the largest contribution compared to wage labor.